2015
DOI: 10.1212/wnl.0000000000002087
|View full text |Cite
|
Sign up to set email alerts
|

A prospective single-blind study of Gamma Knife thalamotomy for tremor

Abstract: Objective: To evaluate the safety and efficacy of unilateral Gamma Knife thalamotomy (GKT) for treatment of severe tremor with a prospective blinded assessment.Methods: Fifty patients (mean age: 74.5 years; 32 men) with severe refractory tremor (36 essential, 14 parkinsonian) were treated with unilateral GKT. Targeting of the ventral intermediate nucleus (Vim) was achieved with Leksell Gamma Knife with a single shot through a 4-mm collimator helmet. The prescription dose was 130 Gy. Neurologic and neuropsychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
82
1
7

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 27 publications
2
82
1
7
Order By: Relevance
“…1,9,26,30,35,41 Despite their delivered improvement in tremor, these therapeutic modalities are often accompanied by adverse effects on speech or language. Recently, a meta-analysis demonstrated that speech difficulty occurred in 19.8% of patients after RF thalamotomy and 19.4% after DBS.…”
mentioning
confidence: 99%
“…1,9,26,30,35,41 Despite their delivered improvement in tremor, these therapeutic modalities are often accompanied by adverse effects on speech or language. Recently, a meta-analysis demonstrated that speech difficulty occurred in 19.8% of patients after RF thalamotomy and 19.4% after DBS.…”
mentioning
confidence: 99%
“…This modality of treatment is more established for essential tremor, with prospective studies showing symptomatic improvement in both techniques [95,96]. For PD, however, better results are being reported for focused ultrasound [97,98], with an additional safety of performing a pre-lesioning of the targeted area before thethermal coagulation is done, therefore reducing the risks of undesired side-effects.…”
Section: ) Discussionmentioning
confidence: 99%
“…Lim et al [21] reported 3 PD patients who had sustained tremor relief after GKT. Ohye et al [22] described outcomes in 59 PD patients, while Witjas et al [25] reported 14 PD patients who were enrolled in a prospective single-blind study. Overall, GKT for PD tremor was associated with a small risk of adverse radiation effects, resulting in temporary hemiparesis or dysphasia [18,19,20,21,22,23,24].…”
Section: Discussionmentioning
confidence: 99%